The Alzheimer's Prevention Initiative (2014)
Background: The Alzheimer’s Prevention Initiative (API) is a collaborative research program involving the Banner Alzheimer’s Institute (BAI) and key partners that evaluates promising treatments with the ultimate goal to postpone, reduce the risk of, or prevent the clinical onset of Alzheimer’s disease (AD). API’s preclinical treatment studies focus on cognitively unimpaired people who, based on their age and genetic background, are at the highest imminent risk of developing AD symptoms. Aims include establishing whether cognitive decline can be slowed; relating a treatment’s biomarker effects to clinical outcome; robustly testing the amyloid hypothesis; giving persons at highest risk access to investigational treatments; creating large prevention registries for these and other preclinical trials; and complementing other prevention initiatives. Methods: API includes the following: a) the API Autosomal Dominant Alzheimer’s Disease (ADAD) Trial, conducted in full partnership with Genentech and the University of Antioquia (UdeA), which is evaluating crenezumab in unimpaired ADAD mutation carriers at certain risk for developing early onset AD; b) the API APOE4 Trial, which will evaluate a to-be-selected amyloid-modifying medication or immunization therapy in unimpaired 60-75 year-old apolipoprotein E4 (APOE4) homozygotes, who are at the highest genetic risk for developing AD at older ages; c) the Colombian API Registry, created by the UdeA in conjunction with BAI and Genentech, which includes >3,300 members of an extremely large ADAD kindred, providing a resource for enrollment into the API ADAD Trial and for biomarker and cognitive studies of ADAD; and d) the Alzheimer’s Prevention Registry (www.endALZnow.org ), a web-based resource that aims to enroll >250,000 individuals who are interested in Alzheimer’s prevention research, facilitates enrollment into AD prevention studies, and provides regular communication to members. Results: We launched the ADAD Trial in 2013 and continue to: characterize the preclinical trajectory of early-onset and late-onset AD in our ADAD and APOE cohorts; establish composite cognitive endpoints; estimate sample sizes using biomarker and cognitive endpoints; vet treatment options; engage academic, industry, and regulatory stakeholders; expand the registries; and prepare for our APOE4 Trial. Conclusions: We will review our progress and plans and address our approach to genetic risk disclosure, cognitive endpoints, recruitment, and data and sample sharing plans.